Protection of Tondano Watershed and Plastic Waste Hazard to the Environment - Fanny Silooy; Henneke Pangkey (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2021)
The Tondano watershed is a very important natural resource and has a strategic function for the surrounding area up to the city of Manado. However, lately there are many problems that occur in the Tondano watershed. The activity of community partnership program for the PKK group of women in the Pinaesaan Kelurahan is carried out, to refresh the knowledge of the existence and sustainability of the Tondano watershed and to recycle the 2 L plastic bottle waste for simple aquaponic activities.Keyword: Tondano Watershed, plastic waste, sustainability, PKK groupABSTRAKDaerah aliran sungai (DAS) Tondano merupakan sumberdaya alam yang sangat penting dan memiliki fungsi strategis bagi daerah sekitarnya sampai ke kota Manado.Â  Namun demikian, akhir-akhir ini terdapat banyak permasalahan yang terjadi di DAS Tondano. Kegiatan program kemitraan masyarakat bagi kelompok ibu PKK di Kelurahan Pinaesaan dilakukan untuk penyegaran kembali tentang eksistensi dan keberlanjutan DAS Tondano serta mendaur ulang limbah botol plastik kemasan 2 L untuk kegiatan akuaponik